2018
DOI: 10.1002/chem.201803076
|View full text |Cite
|
Sign up to set email alerts
|

Extremely Long Lived Localized Singlet Diradicals in a Macrocyclic Structure: A Case Study on the Stretch Effect

Abstract: Localized singlet diradicals have attracted much attention, not only in the field of bond-homolysis chemistry, but also in nonlinear optical materials. In this study, an extremely long lived localized singlet diradical was obtained by using a new molecular design strategy in which it is kinetically stabilized by means of a macrocycle that increases the molecular strain of the corresponding σ-bonded compound. Notably, the lifetime of this diradical (14 μs) is two orders of magnitude longer than that of a standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 87 publications
1
12
0
Order By: Relevance
“…As predicted by the computations, the singlet diradical S- DR3b was extremely long-lived with a lifetime approximately 1000-fold that of S- DR2b ( τ 293 = 209 ns), 49 and 11-fold that of S- DR3a ( τ 293 = 14.2 μs). 68 Thus, the experimental results demonstrate that the stretch effect induced by the macrocyclic structure increases the kinetic stabilisation of the singlet diradicaloid.…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations
“…As predicted by the computations, the singlet diradical S- DR3b was extremely long-lived with a lifetime approximately 1000-fold that of S- DR2b ( τ 293 = 209 ns), 49 and 11-fold that of S- DR3a ( τ 293 = 14.2 μs). 68 Thus, the experimental results demonstrate that the stretch effect induced by the macrocyclic structure increases the kinetic stabilisation of the singlet diradicaloid.…”
Section: Resultsmentioning
confidence: 79%
“…As predicted by the computations, the singlet diradical S-DR3b was extremely longlived with a lifetime approximately 1000-fold that of S-DR2b (s 293 ¼ 209 ns), 49 and 11-fold that of S-DR3a (s 293 ¼ 14.2 ms). 68 Thus, the experimental results demonstrate that the stretch effect induced by the macrocyclic structure increases the kinetic stabilisation of the singlet diradicaloid. Variable temperature laser ash photolysis (VT-LFP) measurements were conducted at ve temperatures in the range of 273-303 K. The activation parameters E a , log A, DH ‡ , DS ‡ , and DG ‡ 293 of the ring-closing reaction of S-DR3b to CP3b in benzene were determined by the Arrhenius and Eyring plots (Table 4, Fig.…”
Section: Time-resolved Absorption Spectroscopymentioning
confidence: 79%
See 2 more Smart Citations
“…In the past two decades we have studied the electronic, stretch, and steric effects on the reactivity of 2,2‐dialkoxy‐1,3‐diarylcyclopentane‐1,3‐diyls (S‐ DR1) generated in the photodenitrogenation of the corresponding azoalkanes AZ1 (Scheme ). These studies have shown that the alkoxy group greatly influences the lifetime of S‐ DR1 (Table ).…”
Section: Introductionmentioning
confidence: 99%